Development of E-Modules Based on Project Based Learning on Virus Material to Improve Students' Creative Thinking - Zulfiani; Yuke Mardiati; Istiadzah Darmastuti (Quagga: Jurnal Pendidikan dan Biologi, 2025)
The existence of teaching materials, namely e-modules, followed by the need for adaptive technology, is needed to optimize learning. This research aims to produce an electronic module (E-Module) based on project-based learning of virus material to improve students' creative thinking. The research used the ADDIE (Analyze, Design, Development, Implementation, Evaluation) development model and used all five stages. The development process goes through expert validation stages, readability testing, student responses to electronic modules in field trials, and n-gain testing. Four experts and a practitioner validated the development results, readability testing with 20 students and field trials with 36 students. The research results show that the total average percentage of electronic module media validation is 85,83% with a very good predicate. Meanwhile, the total average percentage of electronic module material validation was 92.3%, with a very good predicate. The readability test results were 97.56% with a very good predicate. The response results of 36 students to the electronic module were 97.26%, with a very good predicate. Apart from that, there was an increase in students' creative thinking after using the electronic module, namely 0.45 with moderate n-gain criteria. Based on the research results, the electronic module developed is suitable for biology learning with virus material to improve students' creative thinking.